Effect of dynamic vents on the thermal comfort of a passenger car - Singh, Om Prakash (Strojniški vestnik, 2015)
When a vehicle is parked under the direct sun, heat flux entering the cabin through the roof top becomes higher and thus, sets up high temperature gradients beneath the roof. Dynamic airvents are provided to cool the cabin when the air-conditioner is switched on. Unfortunately, the car manufacturer does not specify any guidelines for the driver/passengers regarding the use of dynamic airvents in cars. This study aims to investigate the effect of dynamic vents on the cabin temperature when cooling is initiated. Computational fluid dynamics (CFD) analysis was performed in three stages. In the first stage, temperature data were measured experimentally at various locations in the car and at different times of the day. In the second stage, a 3D CAD model of the same car was generated by measuring the design data. In third stage, a CFD model of the car was developed and used to validate the experimental data. Simulations were performed to study the effect of dynamic vents. The results shows that faster cooling of the cabin and maintaining a uniform temperature distribution inside the cabin is possible at a particular vent angle, which the manufacturer does not specify or indicate for the vehicle. These results suggest an energy saving potential without any changes in the air-conditioning unit itself.
Keywords: dinamični zračniki; klimatizacija; prezračevanje; računalniška dinamika fluidov; temperatura zraka v kabini; toplotno ugodje